Artificial intelligence and audit quality: a comparative study of big four and non-big four audit firms in sri lanka - Tharsika, K.; Varanitha, S.; Thaneshan, G. (University of Jaffna, 2025)
Investors and other stakeholders are becoming increasingly dissatisfied as audit quality in the modern day continues to fall short of the necessary criteria. Simultaneously, financial reporting and auditing on a global scale have been revolutionized by artificial intelligence (AI). In addition, previous studies have not comprehensively explored the influence of AI on audit quality and whether auditors' perceptions of AI's significance in auditing quality differ between Big Four (B4) and non-Big Four (NB4) audit firms, especially in Sri Lanka. Therefore, the purpose of this study is to find out how Sri Lankan auditors view the use of AI in enhancing audit quality and whether the B4 and NB4 audit firms have different perspectives on how AI usage affects audit quality. A Google Form was used to send a standardized questionnaire to auditors working for both types of audit firms in order to collect data for a later study. An independent samples t-test and descriptive statistics are used in this study to evaluate the objective of research. The findings indicate that auditors in Sri Lanka, from both B4 and NB4 firm, perceive that AI has the potential to significantly enhance audit quality. It affirms that there is no substantial disparity in the perspectives of Sri Lankan auditors from B4 and NB4 firms about the beneficial effect of AI on audit quality. This research enhances the current body of knowledge and educates policymakers.
Keywords: Audit Quality; Auditor Perceptions; Artificial Intelligence (AI) in Auditing